Crystallisation and glass transition behaviour of Chilean raisins in relation to their sugar compositions. (1st May 2020) - Truong, Tuyen; Dahal, Deepa; Urrutia, Paulina; Alvarez, Lorena; Almonacid, Sergio; Bhandari, Bhesh
Highlights: Glucose concentration in the initial raisins is readily in supersaturation zone. Glass transitions temperatures (Tgs ) of the Chilean raisin varieties were measured. The glucose:water and fructose:glucose ratios influenced the Tgs of the raisins. The low storage temperatures delayed sugaring as per X-Ray Diffraction results. Abstract: The effects of sugar component ratio, water fraction, and storage conditions on crystallisation and glass transition temperature (T g ) of three Chilean dried raisins were examined by using differential scanning calorimetry (DSC), polarised light microscopy and X-ray diffraction (XRD) techniques. Thompson, Flame and Golden raisins differed in fructose:glucose and glucose:water ratios, impacting on their measured T gs ( P  < 0.05) and propensity of sugaring. The ratios of fructose:glucose (1:3, 1:2 and 1:1) and glucose:water (1.7, 1.9 and 2.1) also influenced the measured T gs ( P  < 0.05) and sugaring of fructose-glucose-water model solutions. Measurement of T gs in the raisins as a function of water activity (aw 0.11–0.74) showed that water acts as a strong plasticiser decreasing the T gs (−16.4 to −61.6 °C). XRD results revealed that sugaring in Thompson raisins was delayed at low temperatures (5 & 15 °C) compared to that stored at 25 °C. The refrigeration may be a simple approach to delay the sugaring in raisins.